Co-producing criminal justice: executive summary - Weaver, Beth (Report, 2012)
This literature review was requested by the Community Justice division of the Scottish Government to advise on and inform the development of a user engagement strategy for criminal justice policy and practice. The purpose of the review was to provide an overview of existing research evidence relating to the concept, practice and value of user engagement in criminal justice policy and practice. In accordance with that aim it was agreed that the review should provide: A definition of user engagement; A review of the available evidence for or against user engagement, giving particular attention to evidence arising from the Risk-need-responsivity literature, the Desistance literature, and the Good Lives literature.